2016
DOI: 10.14391/ajhs.11.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Japanese Nurses’ Tolerance Toward Indonesian Nurse Trainees

Abstract: Objectives: This study aimed to clarify factors related to Japanese nurses' tolerance toward Indonesian nurse trainees.Methods: We conducted a self-administered questionnaire survey from May 21, 2015 to June 13, 2015 targeting Japanese nurses in a hospital accepting Indonesian nurse trainees.Results: We received responses from 97 of the 109 participants (collection rate: 89%, valid response rate: 100%). "Length of education," "overseas travel experience," "number of countries traveled," "length of stay," an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This research identified the average normal culture shock of 83% care giver working nursing home in Japan. The results Sae Tanaka, Hitomi Matsunaga et al, (2016) reported results a comparative study to the cross-cultural tolerance between Indonesian immigrants of travellers, students, internship, health workers who come to Japan, that the health professional under IJEPA have the highest ability to tolerate cross-cultural to adapt to culture shock. So that they acculturation living in Japan because cross-cultural tolerance skills had been related relevant by graduated from a nursing college or vocational school background with health services job experience history, they have received Japanese culture and language training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research identified the average normal culture shock of 83% care giver working nursing home in Japan. The results Sae Tanaka, Hitomi Matsunaga et al, (2016) reported results a comparative study to the cross-cultural tolerance between Indonesian immigrants of travellers, students, internship, health workers who come to Japan, that the health professional under IJEPA have the highest ability to tolerate cross-cultural to adapt to culture shock. So that they acculturation living in Japan because cross-cultural tolerance skills had been related relevant by graduated from a nursing college or vocational school background with health services job experience history, they have received Japanese culture and language training.…”
Section: Discussionmentioning
confidence: 99%
“…That condition Japan is causing growing problems for nursing care (Mari Kinkawa et al, 2014). With the signing of the bilateral Economic Partnership Agreement (EPA), Japan also began accepting foreign nurse trainees from Indonesia in 2008 occupancy placement Japan to nurses are working as nurses (kanggo-shi) in hospitals and as caregivers (kaigo fukushi-shi) in nursing homes (Sae Tanaka, Hitomi Matsunaga et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Above all, neither the micro-level EPA study conducted by Ueno (2013) nor the aforementioned studies by Inoue (2007) and Tanaka et al (2016) are situated in the field of or discuss LPP of the EPA scheme, which is the aim of the current study.…”
Section: Studies On the Epamentioning
confidence: 93%